EFFECTS OF VARIOUS LIGHT INTENSITIES ON PHYCOCYANIN COMPOSITION OF CYANOBACTERIUM LIMNOSPIRA FUSIFORMIS (VORONICHIN) NOWICKA-KRAWCZYK, MÜHLSTEINOVÁ & HAUER - kareem , Haider; Alghanmi, Haider (Malaysian Journal of Science, 2023)
Phycocyanin denotes a photosynthetic pigment discovered in Rhodophyta and cyanobacteria, which has been used in medical, industrial, and agricultural applications. In general, phycocyanin production by cyanobacteria depends on many environmental conditions, mainly light during the cultivation period. The goal of this research was to see how various light intensities of 47, 52, as well as 60 µmol m-2 s-1, affected the Phycocyanin production of cyanobacterium Limnospira fusiformis cultured in Zarrouk medium with a maximum temperature of 28°C. The outcomes revealed that with mild light intensity (52 µmol m-2 s-1), increased phycocyanin production of 11.94 ng/mg took place. With regard to greater light intensity (60 µmol m-2 s-1), the lesser phycocyanin production of 0.57 ng/mg took place. These results give a good impression that moderate lighting increases phycocyanin production, but high light intensity inhibits it. The statistical analysis results also showed that there are significant differences between the light intensities used in the study at a level of p<0.05. Therefore, this study concluded that phycocyanin was affected by light intensity. Light regime optimization gives a good yield of this pigment. In this study, high phycocyanin production by cyanobacterium Limnospira fusiformis occurred in mild light intensity (52 µmol m-2 s-1).